Bureaucratic Readiness in Managing Local Level Participatory Governance: A Developing Country Context. Issue 2 (18th May 2017) - Waheduzzaman, Wahed; Van Gramberg, Bernadine; Ferrer, Justine
Abstract: Participatory governance in developing countries is broadly viewed as an essential prerequisite for successful implementation of public projects. However, it poses many challenges for public bureaucrats in terms of their skills and willingness to engage citizens. Despite the growing evidence of the pervasiveness of participatory governance, research to date has not explored bureaucratic readiness to adopt participatory practices. This research presents findings of a bureaucratic readiness assessment for participatory governance in Bangladesh by exploring how public bureaucrats perceive the value of participation; how they are educated to collaborate with stakeholders; and the extent to which their attitudes are amenable to enhancing participatory governance. Our findings suggest that we can classify readiness in terms of both motivational and educational factors. The study has implications for how readiness can be developed in public officials that may assist in fostering participatory governance in Bangladesh and be informative to other countries experiencing similar issues. Abstract : This paper presents findings of a bureaucratic readiness assessment to measure participatory governance in a developing country context. It reveals that government bureaucrats are not adequately prepared in terms of their motivational and educational skills, which consequently impedes the successful implementation of participatory governance in Bangladesh.